The causes of inefficiency of councils in small cities and its consequences in not realizing sustainable urban development - mahboob reyhan; mohsen ahadnejad; taghi heydari; mortaza shahbazi (اکولوژی انسانی)
The lack of specialized forces in urban affairs in the Islamic councils, including in the city of Kalvanagh, is a fact that has perfect the way for the weakening of the councils. Some of the councils have not even had a day's experience in the field of urban management. Therefore, it is not possible to expect that city managers, delegate of city affairs of those who basically have no experience in the field of city management. according to the purpose of the research, the qualitative research method (grounded theory which includes three types of open, central and selective coding) has been used. In this connection, in order to collect data for two groups, data was collected in two stages.In the first stage, the interview method and questionnaire were used for the group of citizens (n=196) and then the grounded theory was used to analyze the data collected from the questionnaire and the results from the interview. In the second stage of the research, data was collected using the method of interviewing experts (n=20) and for analyzing the data of this stage, the coding technique of grounded theory was used. The results of the analysis of the findings in both groups of citizens and experts show that the main attention of the activity of the city council of kalvanagh in field of physicals district of the city, such as the asphalting of roads, which is more visible to the citizens, and in other districts, such as the economic, environmental, and social fields. And … It has not been efficient. Therefore, it is suggested that the performance of the council can be increased by teaching some specific knowledge, attitudes and skills to the members of the city council